The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.15376/biores.9.1.256-272
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Citronella Oil Extraction Methods from Cymbopogon nardus Grass by Ohmic-heated Hydro-distillation, Hydro-Distillation, and Steam Distillation

Abstract: A proposed method for citronella oil extraction was developed with the application of ohmic heated hydro-distillation. The objective was to compare the performance of three different extraction methods, viz. ohmic heated hydro-distillation, hydro-distillation, and steam distillation. The maximum amount of extracted oil yield by ohmic heated hydrodistillation was 7.64 mL/kWh as compared to hydro-distillation and steam distillation methods that resulted oil yields of 3.87 mL/kWh and 1.69 mL/kWh, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
(23 reference statements)
1
12
1
Order By: Relevance
“…In addition, the clove and cinnamon EOs had the same main active ingredient eugenol at 81.55% and 98.45%, respectively. Sruthi et al (2014) and Uddin et al (2017) reported that the clove and cinnamon EOs contained approximately 80% to 90% eugenol analyzed by GC and GC-MS. Silva et al (2011) and Hamzah et al (2013) indicated that citronella grass EO contained the most important substances, including citronellal, citronellol, geraniol, geranial, and limonene. There were more than 80 components (Silva et al, 2011) appearing in the EOs in which the lemon grass EO had the most important substances, mainly citral, limonene, citronellal, β-myrcene, geranial (α-citral), and neral (β-citral).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the clove and cinnamon EOs had the same main active ingredient eugenol at 81.55% and 98.45%, respectively. Sruthi et al (2014) and Uddin et al (2017) reported that the clove and cinnamon EOs contained approximately 80% to 90% eugenol analyzed by GC and GC-MS. Silva et al (2011) and Hamzah et al (2013) indicated that citronella grass EO contained the most important substances, including citronellal, citronellol, geraniol, geranial, and limonene. There were more than 80 components (Silva et al, 2011) appearing in the EOs in which the lemon grass EO had the most important substances, mainly citral, limonene, citronellal, β-myrcene, geranial (α-citral), and neral (β-citral).…”
Section: Resultsmentioning
confidence: 99%
“…Current practices involve the use of general methods of extraction that have been well developed due to the application of advanced technology. These extraction methods are known as Soxhlet extraction [43]- [45], microwave-assisted extraction [22], [44]- [50], ultrasound extraction [33], [34], [51], supercritical fluid extraction [11], [20], [27], [52], [53], hydrodistillation [22], [24], [44], [49], [54], [55] and steam distillation [14], [52], [56]- [62], [63], [64]. Each process is unique in terms of the process principal and process parameters, however the selection basis is generally depending on the yield of the process [52], [59], [65].…”
Section: Extraction Methods For Conventional Processesmentioning
confidence: 99%
“…C. citratus is first harvested in the range of four to six months upon plantation followed by subsequent harvests in the interval of two to three months [4], [16]. Likewise, C. nardus is ready for harvest after six to eight months of planting but the subsequent harvesting can be done within 90 to 120 days [14], [17], [18]. Nevertheless, the numbers of harvest for both species are subject to the growth of plants.…”
Section: Cultivation Harvesting and The Processing Of Cymbopogon Spmentioning
confidence: 99%
“…In the present study, essential oil from C. nardus contained monoterpenes, such as geraniol (72.71%) and citronellal (49.14%) ( Table 2). According to De Toledo et al (2016) and Hamzah et al (2014), the major component of C. nardus essential oil is oxygen-containing monoterpenes such as citronellal, citronellol, geranial, geraniol, and citral. These compounds work synergistically as repellents (Nerio et al 2010).…”
Section: Repellent Activitymentioning
confidence: 99%